Jung contribution to our time - "Rohrbach, Elizabeth C.(ed.)" (New York, 1967)
This book defines the Jung's contribution such as I. General discussion of the energic viewpoint in psychology a Introduction b The possibility of measurement of psychic quantity 1. .The subjective system of values 2. The objective measure of quantity II. The application of the energic standpoint a The psychological theory of energy b The conservation of energy c Entropy d Energism and dynamism III. The fundamental concepts of the libidotheory a Progression and regression b Extraversion and introversion c The transformation of libido d Symbolmaking .
Keywords: Psychology